Penggunaan Media Digital sebagai Alat untuk Meningkatkan Literasi Kewarganegaraan dan Etika di Kalangan Remaja - Kaka, Margareta Ambu; Zebua, Seruan Hati; Bahagia, Yasinta Avni; Lisa, Rachel Fetriana; Puja, Amanda (CV. Kurnia Grup, 2025)
This study aims to examine the role and use of digital media in improving civic literacy and social ethics among adolescents. The rapid development of information technology has made digital media an integral part of everyday life, including for adolescents. However, unwise use can pose new challenges, such as the spread of hoaxes, cyberbullying, and the loss of social ethics. Through a literature review method, this article analyzes various previous studies on the effectiveness of digital media in promoting civic values, ethics, and public participation. The results of the study show that digital literacy is a key prerequisite for digital media to function optimally as an educational tool. With the right approach, digital media can be an effective means of fostering civic awareness and adaptive social ethics in the modern era.